Impact of the Energy Crisis on the Academic Performance and Professional Training of Undergraduate Students in the Social Work Program in Ecuador - Mendieta Lucas, Lourdes Monserrate; Jaramillo, Jose Gregorio Salazar; Munoz Sanchez, Christopher Fernando (Journal of Posthumanism, 2025)
This research examines the impact of the energy crisis on the academic performance and professional training of 330 Social Work students in virtual and distance learning modalities at two Ecuadorian universities. Employing a mixed methodological approach (quantitative and qualitative), with a non-experimental, cross-sectional, and observational design, the study explores how the crisis affects their preparation to intervene in vulnerable contexts. The results show that the crisis significantly hinders access to virtual education and digital resources, negatively impacting attendance, assignment submission, and study time, exacerbating educational inequalities. Effects are also observed in pre-professional internships, generating stress, demotivation, and even the consideration of dropping out of studies. Finally, a perceived decrease in the quality of training is evident, coupled with a lack of effective institutional support to mitigate the effects of the crisis.